Dietary Self-Selection by Laying Hens Offered Choices of Feed - Hamid, Ramlah; Hutagalung, R. I.; Vohra, P.N (1989)
A short telm dietary self-selection experiment (28 days) was conducted with laying hens fed three treatments (Tl-T3) consisting of a commercially available layer feed (1'1, single choice), commercially available layer feed and oyster shell grit offered separately (T2, two choices) and a com mixture, soyabean meal mixture and oyster shell grit offered sejJarately (T3, three choices). Measurement of feed intake was divided into three feeding periods, from 0800-1200h, 1200-1600h and 1600-0800h. Feed and water' were available ad Ii bitum. Hens were raised under' 15 hour Photo period. Feed, energy and protein intakes were significantly better' on the commercial diet and lower in the other' two treatments. Calcium intake was significantly lower on the single choice and three choice diets. In all treatments, the hens tended to consume more feed during the pel10d between 1600-0800h (40.8-45.8% feed consumed), that is very late in the evening and very early in the morning. Similar amounts of feed (26.2-29.7% of feed consumed) were consumed between 0800-1200h and 1200-1600h. egg production, egg mass and feed conversion were significantly better' on the two and three-choice diets as compared to the single diet. There was no difJeI'ence in egg weight among the three treatments.